Ultrastructural examination of broncho-alveolar lavage for diagnosis of pulmonary histiocytosis X: Preliminary report on 4 cases. Issue 3 (June 1977) - Basset, F; Soler, P; Jaurand, M C; Bignon, J
Abstract : Fibreoptic broncho-alveolar lavage was used in four patients; the diagnosis of histiocytosis X had been established by lung biopsy in three and was suggested on clinical grounds in the remaining patient. Characteristic cells with an ultrastructural cytoplasmic marker (X body) were found in the washes of all four patients. In the patient without biopsy confirmation, the findings in the broncho-aleolar washes supplied the corroborating evidence for the diagnosis. From this preliminary study the technique seems able to provide a diagnosis in pulmonary histiocytosis X without the need for an open lung biopsy.